Karakterisasi mineral magnetik lindi (leachate) TPA Air Dingin Kota Padang menggunakan Scanning Electron Microscopy (SEM) (Characterization of magnetic leachate mineral at TPA Air Dingin Padang City using Scanning Electron Microscopy (SEM)) - Yosi Apri Malita; - Ratnawulan; Fatni Mufit (Department of Physics – Universitas Negeri Padang UNP, 2015)
Waste management in Indonesia is still mixed, between organic and inorganic materials and also have very high landfill waste. Increased precipitation will adversely affect the trash heap, where organic materials in the garbage will decay and will produce liquid waste. In order to manage waste properly at the end should require a final disposal (TPA) so that leachate generated from the decomposition of garbage can be channeled properly in pools shelters located in landfills is called leachate pond. In this research, the characterization of magnetic minerals leachate TPA Air Dingin Kota Padang. This study aims to look at the morphology and elemental composition of the leachate at six points on the leachate pond and river sampling, and sewer landfill. Characterization of magnetic minerals is done using a Scanning Electron Microscope (SEM) aims to look at the morphology , followed by Energy Dispersive spectroscope (EDS) aims to determine the elemental composition . This study used 10 samples taken from six points leachate ponds and 4 points of the river, and sewer . Leachate, rivers , and gutter first extracted with methanol using bath soap which aims to separate the magnetic and non-magnetic minerals. Magnetic mineral morphology analysis using SEM known , that the leachate, rivers , and ditch generally spherical mineral and square and there are many rengkahan . In addition, the size of grains of magnetic minerals belong to the group multidomain ie measuring >20 µm . The results of EDS analysis showed some dominant element in the leachate , rivers , and gutters are Fe , O , Ti , Mg , Al , C , and Si